The Impact of Oil Type on the Performance of β-Amyrin-Based Oleogels: Formation, Physicochemical Properties, and Potential Correlation Analysis - Shuxian Su; Si Qin; Huiping Xia; Peiwang Li; Haiyan Li; Chenjia Li; Shiyin Guo; Chaoxi Zeng (Foods, 2024)
Pentacyclic triterpenes show potential as oleogelators, but their combination with various vegetable oils has limited research. This study selected linseed, rapeseed, sunflower, coconut, and palm oils to combine with the triterpenoid compound β-amyrin for the preparation of oleogels. The stability, crystal network structure, and other properties of each oleogel were evaluated. The correlation between different oil types and the properties of corresponding oleogels was explored. The results showed that β-amyrin formed stable oleogels with five vegetable oils under suitable temperature conditions, wherein especially the LO-based oleogel not only exhibited higher oil-binding capacity and hardness, but also demonstrated excellent stability at the microscopic level and notable rheological properties. Further analysis revealed a close correlation between the physicochemical properties of the oleogels and lipid characteristics, indicating that oleogels prepared from long-chain highly unsaturated fatty acids exhibit high stability. The above results indicate that β-amyrin can be a novel candidate oleogelator and that the oil type can modify the properties of β-amyrin-based oleogels. This study provides the latest reference for the application of pentacyclic triterpenoids in food.